Cloud Computing Accounting Information System Design of Business Entity Village Owned (BUMDESA) - Utama, Anak Agung Gde Satia; Rahayu, Puput Puji (International Journal of Engineering and Management Research, 2023)
This study aims to design an accounting information system for business entities—Village-owned (BUMDesa) Ketapang Banyuwangi with cloud computing. BUMDesa Ketapang has experienced good development in the last five years but has not been matched by an effective accounting system. The research methodology used is qualitative exploratory research with PIECES analysis. The results of this study refer to the cash receipt cycle, cash disbursement, and reporting cycle starting from recording transactions from the business unit and reporting to the treasurer then recorded in a journal, posted to a ledger, and producing financial reports in the form of a Financial Position Report, Profit Loss Report, and cash flow statements. The processes shown are data flow diagrams (DFD), flow charts, entity-relationship diagrams (ERD).